Development Model of Tourism Area Based on Local Wisdom in Lake Toba, North Sumatra - Zefri, Zefri; Sanggam, Sanggam (Eduvest - Journal of Universal Studies, 2023)
The problem addressed is that cultural aspects are key in the development of the tourism sector. Data analysis techniques used relevant methods with the research objectives, including seven types of analysis techniques and compilation of analysis results to determine the direction of development, such as: socio-economic environmental analysis; analysis of the Importance Values of cultural resources in the Lake Toba area in Toba Samosir Regency; Content Analysis to describe the communication content about the principles of local wisdom; SWOT Analysis in the Tourism Area Development Strategy of Lake Toba in Toba Samosir Regency. Thus, a concept and formulation of the Development Strategy of the region are obtained. The research results show that the core values of culture of a nation or ethnic group usually reflect the identity of the respective tribe or nation. The core values that remain fixed and apply to all sub-tribes of Batak in any region they are in, namely "Dalihan Natolu" customs, where these customs can penetrate religious barriers into a social unit. It is one of the cultural values that pride the Toba Batak people, namely the philosophy of life, namely the social relationship system "Dalihan Natolu," which is realized in very close kinship relationships based on blood lineage (genealogical) and marriages that are passed down through generations to the present. The Development Model of Lake Toba Tourism Area in Toba Samosir Regency is sustainable tourism area development through strategies that raise local aspirations for global environmental interests to achieve sustainability.